Marine resources with melanogenic regulatory properties: seagrass, seaweed, and marine sponges as anti-melanogenic agents - Diah Tri Utami, Erna Prawita Setyowati, Yosi Bayu Murti, Edy Meiyanto (Journal of Applied Pharmaceutical Science, 2024)
Tyrosinase is a rate-limiting enzyme that is essential for the synthesis of melanin and controls pigmentation in the skin. The most common strategy in cosmeceutical products for skin lightening is the suppression of tyrosinase. Marine substances contain a variety of unique chemical compounds that have the potential to develop into new bioactive compounds as future medications for skin hyperpigmentation therapy. In this review, we summarize 55 compounds from marine resources that have been identified as active in inhibiting tyrosinase enzyme activity from research studies published up to April 2023. Those substances are classified to be very strong, strong, and moderate inhibit tyrosinase activity and melanin biosynthesis. Based on the IC50 value, there are 12 compounds that act as potential anti-melanogenic agents. 7-phloroeckol isolated from Ecklonia cava has the highest tyrosinase enzyme inhibitory activity with an IC50 value of 0.85 μM, while Arenarol isolated from Dysidea arenaria has the most active properties in reducing the synthesis of melanin with an IC50 value of
Keywords: Marine resources, melanin, inhibitor tyrosinase, bioactive compound, depigmentation skin lightening agent